2010
DOI: 10.1002/j.2161-0045.2010.tb00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Measurement of Workplace Sexual Identity Management

Abstract: The purpose of this study was to advance measurement of sexual identity management for lesbian, gay, and bisexual workers. Psychometric properties of a revised version of the Workplace Sexual Identity Management Measure (WSIMM; Anderson, Croteau, Chung, & DiStefano, 2001) were examined on a sample of 64 predominantly White K‐12 teachers. Reliability and validity data support the usefulness of the revised WSIMM for measuring sexual identity management. Additional research is needed to improve measurement of pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Identity stigma is "personal acceptance of sexual stigma as part of one's value system and self-concept" (Herek, Gillis, & Cogan, 2009), and identity affirmation is the extent to which an LGBT person has positive attitudes and feelings toward their sexual or gender identity (Mayfield, 2001;Mohr & Kendra, 2011). The measure of identity management assesses a series of decision-making processes that reflect a person's efforts to strategically manage their sexual or gender identities in their social network and community (Anderson, Croteau, Chung, & DiStefano, 2001;Lance, Anderson, & Croteau, 2010). Assessments of other general psychological factors such as mastery, perceived resilience, spirituality, and perceived stress are also included in the study.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…Identity stigma is "personal acceptance of sexual stigma as part of one's value system and self-concept" (Herek, Gillis, & Cogan, 2009), and identity affirmation is the extent to which an LGBT person has positive attitudes and feelings toward their sexual or gender identity (Mayfield, 2001;Mohr & Kendra, 2011). The measure of identity management assesses a series of decision-making processes that reflect a person's efforts to strategically manage their sexual or gender identities in their social network and community (Anderson, Croteau, Chung, & DiStefano, 2001;Lance, Anderson, & Croteau, 2010). Assessments of other general psychological factors such as mastery, perceived resilience, spirituality, and perceived stress are also included in the study.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…These early studies despite their methodological limitations have indicated positive relationships between homophobia and workplace distress due to disclosure in the workplace. Furthermore, in terms of understanding disclosure, researchers have investigated self -preservation strategies (more recently termed identity management strategies as mentioned earlier), such as: counterfeiting, avoiding and integrating, which range from denying and limiting identity disclosing information from colleagues or bosses at work, and to disclosing one's sexual orientation or identity and dealing with the associated consequences (see Anderson, Croteau, Ching & DiStefano 2001;Brenner, Lyons & Fassinger 2010;Chrobot-Mason, Button & DiClementi 2002;Lance, Anderson & Croteau 2010). Homophobia, despite being arguably the most popular term used, is argued as not being inclusive enough to encapsulate all the nuances involved in workplace discrimination against GLBT employees.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have suggested that work discrimination has a profound effect on the well-being of this population [9]. This was described by the participants, as they discussed the impact of the discrimination they experienced on their psychological well-being, such as feelings of frustration, and an incoherent identity causing distress.…”
Section: Discussionmentioning
confidence: 98%
“…It could be argued that discrimination in the workplace is an existing barrier that affects LGBT. Researchers have suggested that work discrimination has a profound effect on the well-being of the LGBT population [9]. Work discrimination can be defined as the unjust and negative treatment of workers based on personal attributes that are irrelevant to job performance [10].…”
Section: ) Introductionmentioning
confidence: 99%